MALPRACTICE IN COMPOSITE/MIXED PROSTHESIS - Magda Antohe; Ramona Feier; Doriana Agop Forna; Cosmin Oniciuc; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2015)
The purpose of this study is to indicate the causes of malpractice in composite/mixed prosthetics, by quantifying the main factors related to the particularity of the prosthetic field, to the choice of composite prostheses design, to the choice and application of maintenance, support and stabilization elements in agreement with the treatment principles: prophylactic, biomechanical and biological. The study was based on a number of 170 patients who reported to the Clinical Education Facility of the Faculty of Dental Medicine with various types of prostheses in the field of mixed/composite prosthetics. With regard to the factors favoring malpractice, we noticed a number of 20 cases in which partial rehabilitation was made while preserving the old restorations. A number of 40 cases belonged to an inconsistency between the clinical-biological indicators and the prosthetic solution of choice, 30 cases of malpractice due to failure to observe the biomechanical principle and 10 cases were due to the absence of morphofunctional harmony between the fixed and removable prostheses, out of the total cases under evaluation. Un unwanted aspect of these prostheses is malpractice, which may occur if certain crucial elements related to the prosthetic field are not observed, if certain procedures in the field of non-specific prosthetic therapy are not followed and if the design and biomechanical principle are not complied with. The modern methods of complex oral rehabilitation are mainly indicated by taking into consideration the objectives of the treatment plan in view of restoring the biomechanical balance and the functions of the stomatognathic system. Failure to correlate these methods with the status of the prosthetic field may lead to malpractice.